2011
DOI: 10.1158/0008-5472.sabcs11-s5-6
|View full text |Cite
|
Sign up to set email alerts
|

S5-6: Neoadjuvant Pertuzumab and Trastuzumab Concurrent or Sequential with an Anthracycline-Containing or Concurrent with an Anthracycline-Free Standard Regimen: A Randomized Phase II Study (TRYPHAENA).

Abstract: Background: Pertuzumab (P) is a fully humanized investigational monoclonal antibody that binds to human epidermal growth factor receptor 2 (HER2), preventing homo- and heterodimerization of HER2 and other HER family members and inducing antibody-dependent cell-mediated cytotoxicity. The NeoSphere study demonstrated significantly increased antitumor activity in the neoadjuvant setting for the combination of P and trastuzumab (H) plus docetaxel (T) compared with HT alone (Gianni et al. SABCS 2010), consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…The three arm TRYPHAENA study evaluated neoadjuvant administration of pertuzumab and trastuzumab with sequential or concomitant anthracycline-based or anthracycline-free chemotherapy [53]. A first analysis showed that the dual blockade was safe without increased risk of cardiac events.…”
Section: Dual Blockade Of Her2-signalling With Trastuzumab and Pertuzmentioning
confidence: 99%
See 1 more Smart Citation
“…The three arm TRYPHAENA study evaluated neoadjuvant administration of pertuzumab and trastuzumab with sequential or concomitant anthracycline-based or anthracycline-free chemotherapy [53]. A first analysis showed that the dual blockade was safe without increased risk of cardiac events.…”
Section: Dual Blockade Of Her2-signalling With Trastuzumab and Pertuzmentioning
confidence: 99%
“…6. pCR rates by hormone receptor status in the TRYPHAENA trial [53]. addition to standard neoadjuvant chemotherapy for early stage TNBC (M14-011, EudraCT 2013-002377-21).…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%
“…Importantly, the addition of pertuzumab did not produce any significant drop in the cardiac function (4-5% EF drop across all groups). The second study -TRYPHAENA trial -is only available as an abstract but its importance relies on the fact that it incorporates the trastuzumab + pertuzumab combination to an anthracycline-free regimen [35,36] . One of its three arms use the very popular TCH regimen (carboplatin, docetaxel and trastuzumab) with pertuzumab for six cycles before surgery followed by one year of trastuzumab.…”
Section: Neo-adjuvant Treatmentmentioning
confidence: 99%
“…þ Breast Cancer) study, a total of 225 patients with HER2 þ breast cancer were randomized to receive trastuzumab and pertuzumab in combination with one of three chemotherapy regimens: concurrently with an anthracycline-taxane-containing regimen [FEC (fluorouracil, epirubicin cyclophosphamide)-docetaxel]; after FEC, but concurrently with docetaxel; or concurrently with the docetaxel/carboplatin combination (14). The primary endpoint of the study was safety and tolerability.…”
Section: Neoadjuvant Settingmentioning
confidence: 99%